E-mails spark ethics row - Dalton, Rex (Nature (London), 2010)
[...] Tyrone Hayes, a biologist and faculty member at the University of California, Berkeley, drew from Simmons's lexicon earlier this year while writing a series of 'trash-talking' e-mails to representatives of Syngenta, the world's largest producer of the herbicide atrazine. The chemical is currently the subject of a class action lawsuit launched against Syngenta by 15 water providers in Illinois who are seeking at least $350 million for facilities to purify drinking water of atrazine, which they say poses a threat to human health.